کیتھ میسی کا حروف مقطعات کے بارے میں نظریہ اور اسلامی روایت: تجزیاتی مطالعہ: THE OPINION OF KEITH MESSAY ABOUT MYSTERIOUS LETTERS OF THE QURAN AND ISLAMIC TRADITION: AN ANALYTICAL STUDY - Dr Sumera Rabia; Sadia Arif; Sadaf Siraj (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
Orientalists have also presented their theories and ideas regarding the mysterious letters of the Quran. These theories encompass diverse viewpoints. According to some, these are ancient names of the chapters of the Quran. Some consider them as symbols indicating the central themes of the chapters. Others take them as references to individuals who were associated with these chapters. This article takes Keith Massey’s theory on disjointed letters as the subject of investigation. According to him, the mysterious letters always appear in a specific order. Upon examining the thirteen different disjointed letter combinations found in the Quran, which are present in eleven different chapters, it becomes evident that the presence of letters in these combinations is neither random nor irregular. These letters are actually abbreviations of the names of individuals whom the writers of the Quran have taken the material. The categorisation of individuals’ names could be for any reason, and then these individuals were ranked according to their importance, resulting in these disjointed letters appearing in a specific order and creating a certain structure and regularity.Keith Massey Orientalist